Prevalence of Pulmonary Tuberculosis among Caregivers of Patients with Pulmonary Tuberculosis at TB Sanitorium Kotri - Dr. Kanwal Abbas, Nimerta Kumari, Dr. Fahmida Gul, Dr. Farhana Rajpar, Dr. Waseemullah Sheikh, Dr. Pushpa Goswami (Drugs and Cell Therapies in Hematology, 2022)
Objective: To evaluate active pulmonary tuberculosis among caregivers of patients with pulmonary tuberculosis at TB Sanitorium, Kotri. Methodology: This cross-sectional descriptive study was piloted from July 2017 to December 2017, a total 80 care givers selected by convenient sampling. All the asymptomatic caregivers, of any gender/ age with patient at any time from date of admission to discharge of patient included in this study while those who had past history of TB diagnosed/treated or with symptoms were omitted. Care givers fill the predesigned questionnaire, and then investigated for TB with blood complete picture, Sputum AFB and X-ray chest. Result: Among the total Study population (n=80), frequency (%) of rural population, age over 40 years, relatives and in contact with patient for less than 06 months were in majority. Among the caregivers (n=80), 52(65%) were AFB positive while 28(35%) found with AFB negative, while chest x ray finding observed as apical cavitation, apical consolidation and other TB findings among 41(51.25%), 36 (45%) and 3(3.75%) caregivers Sputum AFB findings compared with chest x ray findings of caregivers by applying chi square test. Statistically significant association has been observed for AFB positive caregivers with gender of caregiver and residential area (p value <0.01 by chisquare test) while no significant association has been found with period of contact and age of caregiver. Conclusion:This study revealed higher frequency of TB chest x ray findings and AFB positivity among family /friend caregivers in contact with active TB cases.